Parent Concern and Awareness of Corticosteroid use in Pediatric Patients with Atopic Dermatitis in Al-Majmaah, Saudi Arabia - Yousef Alrohaimi, Raghad A. Alturki, Atheer A Aljithalin, Renad B Alanazi, Ohood L Almimony (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Atopic dermatitis has been considered a multifactorial disease and is a chronic, relapsing, and highly pruritic skin disease; usually presents with skin itchiness which is considered the most burdensome symptom, followed by skin redness and dryness, chronic pruritus, and sleep disturbance, as well as the time and expense associated with treatment, are often most distressing for patients and families. Atopic skincare and treatment include skin hydration, pharmacologic therapy, and avoidance of relevant triggers. Corticosteroids (TCS) of appropriate strength are considered the first-line therapeutic agent. Objective: To study the parents’ concern and awareness of corticosteroid use in pediatric patients with atopic dermatitis in Al-Majmaah governorate, Saudi Arabia in 2021. Methodology: A community-based descriptive cross-sectional study was performed. The data was collected using an electronic questionnaire and analyzed using SPSS v.23. Results: 403 respondents were enrolled in the study where most of the fathers (46.2%) were within the age group of 30-45 years, and a half (50.6%) of mothers were between 30-45 years. Most children (30%) have itchy skin for 2-3 days per week due to eczema, and 174 (43.2%) have dry, rough skin every day. The mean score for the knowledge and beliefs was 49.8±19.9, 76.6±20.9 for fears, and 72.4±21.8 for behavior. More than one-third of respondents (46.2%) almost agreed that TCS could pass into a child’s bloodstream, and 157 (45.1%) of those who used steroids before almost agreed that it’s beneficial. More than one-third of our respondents (36.2%) always get their information regarding TCS from dermatologists. Marital status significantly affects Topical Corticosteroid Phobia (TOPICOP) score (P-value = 0.003), where divorced have the highest mean score compared to married or widows. Conclusion: The TOPICOP score for mean knowledge and beliefs was slightly lower than the global TOPICOP score. TCS can cause skin damage, as reported by nearly half participants. Slightly less than half of them are afraid of putting cream (TCS) on a child’s skin in certain zones like the chin and the eyelids where the skin is thinner. The most reported information source about TCS for nearly half of the participants was doctors. No statistically significant association was found between participants’ age groups, occupation, and educational level and global TOPICOP score. However, a significant association was found between marital status and TOPICOP score.